2015
DOI: 10.4172/2155-9600.1000430
|View full text |Cite
|
Sign up to set email alerts
|

Modern Diet and its Impact on Human Health

Abstract: The general public's view of modern diet and human health has undergone drastic changes in recent years. There is general harmony that many chronic health problems, first noted in Western countries but progressively flourished worldwide, relate mainly to diet. There is far less consensus, however, about the dietary factors implicated in such health problems. This lack of understanding has opened the door to a propagation of different recommendations as to the best diet for modern humans. Let me note that all h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Many changes in the quality and quantity of food have occurred, and this is a critical medical issue in the modern human population in these societies. According to the literature, modern food affects human health (Shridhar et al, 2015), and females have a significantly higher eating-disorder psychopathology than men (Lydecker and Grilo, 2018). Notably, the quality and quantity of food has been related to SES (Andrea et al, 2017), and the higher the SES, the higher the body weight and more frequent the health problems.…”
Section: Sociocultural Change and Obesitymentioning
confidence: 99%
“…Many changes in the quality and quantity of food have occurred, and this is a critical medical issue in the modern human population in these societies. According to the literature, modern food affects human health (Shridhar et al, 2015), and females have a significantly higher eating-disorder psychopathology than men (Lydecker and Grilo, 2018). Notably, the quality and quantity of food has been related to SES (Andrea et al, 2017), and the higher the SES, the higher the body weight and more frequent the health problems.…”
Section: Sociocultural Change and Obesitymentioning
confidence: 99%
“…The notion of ‘inflammatory foods’ is becoming increasingly recognised across chronic diseases such as RA. The ‘modern diet’ 5 especially practised in Western cultures could be viewed as the greatest enemy of chronic inflammatory conditions like RA, whereby the increased consumption of refined carbohydrates, vegetable oils rich in omega-6 fatty acids and decreased consumption of long-chain omega-3 fatty acids represent ‘the perfect nutritional storm’. 6 Supporting these observations, animal data have confirmed that a low ratio of n-6/n-3 polyunsaturated fatty acids (PUFA) reduces adjuvant-induced arthritis in rats.…”
Section: State Of Knowledgementioning
confidence: 99%
“…And when the bacteria break down in smaller units (viroids; nanobacteria; L. forms and other), the plants can take up these smaller units too. They act as their vitalizers (Rusch, 1968). The breakdown is probably facilitated by the bacteriophages on the slimey surfaces of the root tops (Barr, 2013).…”
Section: Corollarymentioning
confidence: 99%